OPTIMALISASI PELAKSANAAN PROGRAM JAMINAN KESEHATAN NASIONAL MELALUI PENINGKATAN DAN PENGUATAN LAYANAN FASILITAS KESEHATAN PRIMER DENGAN PENDEKATAN GATE KEEPER IN MANAGED CARE DALAM RANGKA PENCAPAIAN UNIVERSAL HEALTH COVERAGE DI KOTA MALANG - Eko Aristanto; Christina Sri Ratnaningsih; Krisnawuri Handayani (University of Merdeka Malang, 2016)
As the site ofthe firstlevel ofhealth care,Puskesmashasarolethat is essential forthe success ofJKNinIndonesia.Therefore,the success of JKN largely determined byPuskesmas, in particulartowards healinga patientthat can coveredinPuskesmas, whichdo not need togeta referenceto thehospital (Rumah Sakit). The main purpose ofthis studyis : the first,identify the availability ofmedicaland non-medical personnelatthe primarylevelhealth facility, identifythe characteristics ofthenationalhealthcareservicesatthe primarylevelhealth facility, identifythe conditions oftheexistance health service of facilities and infrastructureatthe primarylevelhealth facilities.Second,identify procedure anddeliverysystem capital funding onthe primarylevelhealth facility,identify theconstraints andbarriers tohealth servicesatthe primarylevelhealth facility,identify themembershipof nationalhealth coverage, identifyrelatedcommunityperceptions ofhealth servicesatthe primarylevelhealth facility,based onthesetwo steps, thenstrategizeimplementation ofoptimization ofnational healthAssurance Programthrough theenhancement andstrengthen ofprimary healthfacilitiesserviceswith theapproach of theGateKeeperinManaged Carein the framework ofthe attainment ofUniversalHealth Coveragein Malang City. The design of this research is the combination of various research methods which include descriptif research, policy research and action research.Based on the research results, there are still some obstacles and constraints of Puskesmas as the first level health facilities : a) aspects of the service , b) aspects of human resources, c) aspects of management, d) aspects of facilities and infrastructure.